Breaking through the glass ceiling effect of high-grade clinical evidence creation in orthopaedics & trauma - Lewandrowski, Kai-Uwe; Ramírez León, Jorge Felipe; Dowling, Álvaro; Rodríguez García, Manuel; Rugeles, José Gabriel; Ramírez, Carolina; García, Alfonso; Valerio, Jose; Teixeira de Carvalho, Paulo Sérgio; Duchén Rodríguez, Luis Miguel; Moyano, Jaime; Herrera, Mario; et al. (Revista Colombiana de Ortopedia y Traumatología, 2022)
Introduction: Randomization protocols in clinical studies of common orthopedic problems and traumatic injuries are challenging to orchestrate. The lack of high-grade clinical evidence from prospective randomized, double-blinded study design is often cited as a primary reason for rejecting proposed therapy advances in orthopedic surgery. Materials and Methods: This position paper summarizes the clinical trial limitations in surgical subspecialties. We present a consensus statement on how practicing orthopedic surgeon can produce high-quality clinical evidence to affect changes in practice protocols. Results: Our literature review revealed that classifications of level of evidence reporting varies between surgical subspecialties. Research in orthopedic- and musculoskeletal trauma care is primarily directed at the diagnosis, preferred treatment, and economic decision analysis, whereas other prognosis-based classifications are preferred in other areas such as plastic surgery. In orthopedics, controlled double-blinded randomization is rare and often unpractical or unethical for a placebo control purpose where patients may be harmed. Crossing over between study groups randomized surgical trials is common. Other obstacles in surgical trials range from lack of organizational and financial support, institutional review or ethics board approval, and registration requirements for clinical trials to insufficient time left outside an already busy clinical schedule to dedicate to this laborious uncompensated task. Conclusion: Orthopedic surgery is as an experience- and skill-based subspecialty. Many innovations start with entrepreneur surgeons as reporting of opinions or retrospective cohort studies many of which suffer from bias. Prospective observational cohort studies with consistent results may offer higher-grade clinical evidence than poorly executed randomized trials.